The Growth of Mangroves in Created Wetland in the Porong River, East Java, Indonesia - Hamzah, Faisal; Widakti, Nuryani; Sidik, Frida (Department of Agronomy and Horticulture, IPB University, 2015)
Mangrove plantation projects have been established in the created mangrove wetland in the mouth of the Porong River, East Java, in parallel with the construction of reclamation area for LUSI mud dumping area. This study was aimed to assess the growth of planted mangrove in a created mangrove wetland in relation to the environmental parameters, which are sediment salinity, sediment fraction, pore water salinity, pH/eH, and total organic matter (TOM) in the sediment. Periodical measurement of mangrove growth Avicennia sp. and the environmental parameters were undertaken in the created wetland and in the mud flats of intact mangrove forest nearby the created wetland as the natural reference in July to November 2012. We found that sediments in the created wetland had different characteristics of sediment fractions, sediment salinity and TOM compared to sediments in the mud flats of intact forests. Sand dominated sediments with low TOM and higher water salinity in the created wetland as compared to those in the mud flats affected growth rate of mangroves in study sites. We suggest that TOM and salinity are important factors that contribute to the growth of mangroves in the Porong River. Keywords: Mangrove, salinity, Porong River, total organic matter.